2017
DOI: 10.2139/ssrn.3175365
|View full text |Cite
|
Sign up to set email alerts
|

Physical Disability and Labor Market Discrimination: Evidence From a Field Experiment

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 17 publications
1
8
0
3
Order By: Relevance
“…How do employers incorporate such rights into their hiring practices? A paradox in research on employer attitudes and hiring practices in relation to disabled people is that employers often express positive attitudes (Burke et al, 2013;Ju et al, 2013) but show negative hiring intentions and behaviour (Baert, 2014;Araten-Bergman, 2016;Ameri et al, 2018;Bellemare et al, 2018;Shamshiri-Petersen and Krogh, 2020;Bjørnshagen and Ugreninov, 2021). Bredgaard (2018) underlines the importance of not conflating behaviour and attitudes, and proposes a model uniting a behavioural and an attitudinal dimension.…”
Section: Regulatory Approa Ches To Employer Engagementmentioning
confidence: 99%
“…How do employers incorporate such rights into their hiring practices? A paradox in research on employer attitudes and hiring practices in relation to disabled people is that employers often express positive attitudes (Burke et al, 2013;Ju et al, 2013) but show negative hiring intentions and behaviour (Baert, 2014;Araten-Bergman, 2016;Ameri et al, 2018;Bellemare et al, 2018;Shamshiri-Petersen and Krogh, 2020;Bjørnshagen and Ugreninov, 2021). Bredgaard (2018) underlines the importance of not conflating behaviour and attitudes, and proposes a model uniting a behavioural and an attitudinal dimension.…”
Section: Regulatory Approa Ches To Employer Engagementmentioning
confidence: 99%
“…It is well established that discrimination toward those with disabilities is embedded in structural and interpersonal aspects of social life (Dirth & Branscombe, 2017). For example, Bellemare et al (2018) found that job applicants who disclosed a physical disability in their application were less likely to receive a call-back for a job interview. Our results illuminate the discrimination that youth in high school already experience, which has implications for shaping their transition to adulthood, including transitions to postsecondary education and employment.…”
Section: Discussionmentioning
confidence: 99%
“…6 Other components include included gender (when relevant), availability of a government sponsored subsidy, and work history (years of experience, unemployment spells). An unpublished working paper using data from the benchmark experiment documents that none of these variables significantly determine callback rates (see Bellemare et al (2018) for details). The computer program ensured consistency between all components of the CV.…”
Section: Benchmark Experimentsmentioning
confidence: 99%